Incidentally diagnosed placenta accreta managed conservatively in a primigravida: case report and review of literature - Kumari, Om; Gaurav, Amrita; Khoiwal, Kavita; Gupta, Anshu; Kapur, Dhriti; Halder, Rashmi; Chaturvedi, Jaya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Placenta accrete spectrum (PAS) disorder is rarely reported in primigravida woman without recognisable risk factors. It can be encountered intraoperatively without prior suspicion. Massive obstetric haemorrhage and increased maternal morbidity and mortality is often associated with emergency caesarean hysterectomy. We presented a 26-year-old primigravida who was presented to our institute as post-dated pregnancy in labour with no other comorbidities. She was taken up for cesarean section in view of prolonged labor. After birth of the baby, the placenta failed to separate on its own and could not be delivered with gentle controlled cord traction and uterine massage. Placenta was seen bulging out at left cornuo-fundal site as boggy mass in serosa of uterus as bluish distended placental bulge suggestive of placenta accreta. Placenta was left in situ and postoperatively uterine artery embolisation was done. Post-operatively patient did not develop any complications and follow up period of 6 months was uneventful. Conservative management of PAS can be judiciously contemplated in primiparous women desirous of fertility preservation and uterus conservation. The woman needs to be emphasised upon need for close follow up and risk of haemorrhage and sepsis till complete resorption of placenta occurs.